PERLINDUNGAN KONSUMEN PERUMAHAN DALAM JUAL BELI RUMAH DENGAN SISTEM PRE PROJECT SELLING - Jhon Haward Hutagaol; Anna Maria Tri Anggraini (Fakultas Hukum Universitas Trisakti, 2021)
Developers make more sales using the pre-project selling system, in which developers start selling before the project is built, where the properties being sold are still new in the form of images or concepts, but in the course of transactions with the system, many consumer rights are violated by business actors. Based on this, the author discusses the problem of consumer rights being violated and efforts to restore Darwin's consumer rights based on Supreme Court Decision Number 653 K/Pdt.Sus-BPSK/2021. This article uses normative research, using secondary, primary legal, and tertiary legal materials. The author concludes that there is a discrepancy in the transaction between Darwin and PT Buana Cipta Propertindo, thereby violating consumer rights as stated in Law number 8 of 1999 concerning Consumer Protection and laws and regulations in the housing sector. The author also considers that the Supreme Court Decision which annulled BPSK and Batam District Court decisions does not support efforts to restore consumer rights and does not accommodate the Consumer Protection Act because BPSK should have the ability and authority to examine the dispute between Darwin and PT Buana Cipta Propertindo based on an agreement.